2021
DOI: 10.1097/cad.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological response with diabetic ketoacidosis to the combination of sintilimab and anlotinib in an unresectable hepatocellular carcinoma patient: a case report

Abstract: Most hepatocellular carcinoma (HCC) patients have dismal prognoses because they are already in the advanced stage at the time of initial diagnosis and are unable to undergo upfront surgery. Recent studies of immune checkpoint inhibitors (ICIs) and antiangiogenic agents (AAAs) have shown encouraging results for unresectable HCC (uHCC). Here, we report a patient with uHCC who was treated with a combination of anlotinib and sintilimab (sintilimab 200 mg, intravenous glucose tolerance test, q21d and anlotinib 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For the cases reviewed, the demographic features, clinical manifestations and treatment of irAEs were summarized ( Table 1 ). From these case reports, sintilimab has been shown to induce various immune-associated disorders, including autoimmune diabetes ( 18 , 26 , 30 ), pneumonitis ( 27 , 28 ), pulmonary fibrosis ( 20 ), cytokine release syndrome and multiple organ failure ( 20 , 21 ), myocarditis ( 24 , 29 ), hypothyroid myopathy ( 19 ), myasthenia gravis and myasthenia crisis ( 22 ), paraneoplastic neurological syndrome and enteric neuropathy ( 23 ), psoriasis exacerbation ( 25 ). Some literatures previously indicated that patients with irAEs usually showed a markedly better efficacy than those without irAEs, known as higher overall response rate, longer PFS and better overall survival ( 31 , 32 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…For the cases reviewed, the demographic features, clinical manifestations and treatment of irAEs were summarized ( Table 1 ). From these case reports, sintilimab has been shown to induce various immune-associated disorders, including autoimmune diabetes ( 18 , 26 , 30 ), pneumonitis ( 27 , 28 ), pulmonary fibrosis ( 20 ), cytokine release syndrome and multiple organ failure ( 20 , 21 ), myocarditis ( 24 , 29 ), hypothyroid myopathy ( 19 ), myasthenia gravis and myasthenia crisis ( 22 ), paraneoplastic neurological syndrome and enteric neuropathy ( 23 ), psoriasis exacerbation ( 25 ). Some literatures previously indicated that patients with irAEs usually showed a markedly better efficacy than those without irAEs, known as higher overall response rate, longer PFS and better overall survival ( 31 , 32 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Compared with traditional cytotoxic chemotherapeutics, these agents have higher safety and selectivity profiles, and they have benefited many patients who cannot be cured by surgical operations or who are resistant to common chemotherapeutics ( 58 ). Anlotinib can be used clinically for the treatment of locally advanced or metastatic non-small cell lung cancer, but it also offers a new hope for HCC treatment ( 59 , 60 ). Oral administration has good patient compliance and is usually the preferred route of administration of drugs for the treatment of chronic diseases ( 61 ).…”
Section: Discussionmentioning
confidence: 99%